2019
DOI: 10.12659/msm.915946
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Analysis of a Long Non-Coding RNA (lncRNA)-Associated ceRNA Network in β-Thalassemia and Hereditary Persistence of Fetal Hemoglobin

Abstract: BackgroundHigher fetal hemoglobin (HbF) levels can ameliorate the clinical severity of β-thalassemia. The use of integrative strategies to combine results from gene microarray expression profiling, experimental evidence, and bioinformatics helps reveal functional long noncoding RNAs (lncRNAs) in β-thalassemia and HbF induction.Material/MethodsIn a previous study, a microarray profiling was performed of 7 individuals with high HbF levels and 7 normal individuals. Thirteen paired samples were used for validation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Interestingly, miR-125a-5p and miR-142-3p were among the top 50 most significant HUDEP1_L vs. HUDEP2_L DE miRNAs. Of note, HBBP1 (NR_001589), another lncRNA recently identified as related to high γ-globin levels [ 102 ], is predicted to interact with five HUDEP1_L vs. HUDEP2_L DE miRNAs, including miR-18b-5p (HUDEP1_L vs. HUDEP2_L log 2 FC = 2.99), which was among the top 20 DE miRNAs based on p -value.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, miR-125a-5p and miR-142-3p were among the top 50 most significant HUDEP1_L vs. HUDEP2_L DE miRNAs. Of note, HBBP1 (NR_001589), another lncRNA recently identified as related to high γ-globin levels [ 102 ], is predicted to interact with five HUDEP1_L vs. HUDEP2_L DE miRNAs, including miR-18b-5p (HUDEP1_L vs. HUDEP2_L log 2 FC = 2.99), which was among the top 20 DE miRNAs based on p -value.…”
Section: Resultsmentioning
confidence: 99%
“…LncRNAs act as an endogenous "sponge" or ceRNA interacting with miRNA and exert their biological function by binding to their target genes. 28 To confirm whether lncRNA RP11-422N16.3 interacts with miR-23b-3p, we applied RNA-pull down assay and the results supported the binding relationship between RP11-422N16.3 and miR-23b-3p. As early as the 1950s, Warburg reported that pyruvate, which decomposes glucose in tumor cells, was converted to lactic acid in the presence of oxygen, rather than in the mitochondria, and was later called the "Warburg effect."…”
Section: Discussionmentioning
confidence: 85%
“…A study on the construction of an lncRNA-associated ceRNA network revealed two candidates, NR_001589 and uc002fcj.1, that are significantly expressed in individuals with high HbF levels. The study predicted that these lncRNAs promote the expression of HBG1/2 by sponging miRNA and induce HbF production (Jia et al 2019). Microarray analysis in another study to profile lncRNAs, miRNAs and mRNAs in individuals having hereditary persistence of fetal hemoglobin has elucidated six lncRNAs that competitively sponge miR-486-3p, therefore elevating HbF level (Lai et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some studies have demonstrated the emerging role of lncRNAs in the regulation of fetal hemoglobin (HbF) expression (Ivaldi et al 2018) (Jia et al 2019). It is expected that identification of new lncRNAs would contribute substantially to our understanding of the regulatory mechanisms of the γ-globin genes and hence bring us closer to developing new therapeutic strategies to treat beta-hemoglobinopathies like β-thalassemia and SCA disease.…”
Section: )mentioning
confidence: 99%